2015
DOI: 10.3168/jds.2014-8025
|View full text |Cite
|
Sign up to set email alerts
|

Feeding characteristics and rumination time of dairy cows around estrus

Abstract: Against the background of decreasing reproduction efficiency, estrus detection is gaining increased importance. The objective of this study was to evaluate changes of feeding characteristics and rumination time in dairy cows in the days around estrus. Feeding characteristics were recorded by weighing troughs, and rumination time by acoustic sensors. Analysis included data from 25 primiparous and 37 multiparous cows, which were successfully inseminated (day of insemination=d 0). Feeding time and rumination time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 24 publications
10
43
1
2
Order By: Relevance
“…In contrast, 86.2% of all cows showed decreased rumination time during estrus. Similar results were reported by Pahl et al . using the same measurement system.…”
Section: Estrus Detectionsupporting
confidence: 91%
“…In contrast, 86.2% of all cows showed decreased rumination time during estrus. Similar results were reported by Pahl et al . using the same measurement system.…”
Section: Estrus Detectionsupporting
confidence: 91%
“…Rumination time increased as early as one day later and fluctuated within a narrow range from day 2 to day 30 in agreement with the findings of other studies ( Journet and Remond, 1976;Soriani et al, 2012;Braun et al, 2014;Calamari et al, 2014;Pahl et al, 2014;Hoy, 2015;Clark et al, 2015). The nadir on the day of calving has been attributed to hormonal changes (Pahl et al, 2015), and it is possible that parturition itself reduces rumination activity (Grunert, 1993). In one study, rumination was reduced by 70% on the day of calving (Calamari et al, 2014), and in another, the postpartum rebound was slow (Pahl et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
“…In recent years, there has been interest in determining whether automated technologies, including rumination measurements, could be used to supplement or replace visual detection of estrus. Pahl et al (2015) reported for 25 primiparous and 37 multiparous cows a decline in eating time and rumination time on the day before and the day of insemination compared with the baseline days. Differences were greatest on the day before insemination, which would suggest that this information could be used to help improve timely insemination.…”
Section: Estrus Detectionmentioning
confidence: 94%